MAQASHID SYARIAH DALAM PENERAPAN PAJAK KHARAJ PADA MASA UMAR BIN KHATTAB RA - Muhammad Riza (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2017)
The policy on the spoils of war made as assets of the State and the original owners will be subject to land tax (kharaj) is a form of stabilizing the State’s economy. The application of kharaj to all non-Muslims becomes a debate. Does it include the purpose of sharia (maqasid shariah) or not?. The purpose of this study is to explain the use of the concept of maqasid shariah and its applica- tion in the matter of land tax (kharaj) at the time of Caliph Umar bin Khattab RA. The research method that the writer uses is descriptive qualitative method by studying classical books as main source plus secondary source from various books, journals and other scientific articles. The results of this study show that the caliph Umar using maqasid shariah in establishing the implementation of kharaj policy for the benefit of the ummah. And the application of the shariah maqasid method is very relevant to the application of kharaj, considering the long-term benefits and can be felt equally for all levels of society and future generations.